Hipertensi Dengan Kejadian Jatuh Pada Lansia: Studi Kajian Pustaka: Hipertensi Dengan Kejadian Jatuh Pada Lansia: Studi Kajian Pustaka - Yasa, Kadek Andre; Negara, Anak Agung Gede Angga Puspa; Kamayoga, I Dewa Gede Alit (PT. Kesehatan Gerak Fungsi Tubuh, 2024)
Background: Falling is a condition when a part of the body comes into contact with the ground or floor. The incidence of falls in the elderly is approximately 30-50%.. Hypertension is an intrinsic factor in the occurrence of falls because it affects the body's awareness and balance. Therefore, the authors reviewed the articles to find out the relationship between hypertension and the incidence of falls in the elderly. This study aimed to determine the relationship between hypertension and the incidence of falls in the elderly. Methods: This study used a literature review design to discuss the hypertension and falls in the elderly. Journals were obtained by accessing the Google Scholar and PubMed databases using the keywords elderly, hypertension, falls. Search for journals based on inclusion criteria which includes: year of publication of the article in the last 10 years, journal articles in the open access category and full text articles. Exclusion criteria include: if there are articles that are the same, then other articles will be executed, abstracts, theses, and theses. Results: Based on the four reviewed journals, it was found that history of hypertension affects the incidence of falls in the elderly. The highest incidence of falls is experienced by the elderly in the old or old category, namely aged 75-90 years and the most dominant is experienced by the elderly who are female. Conclusion: There was a possible relationship between hypertension and the incidence of falls in the elderly. Further study may find the correlation and risk factors of the hypertension to the falls incidence among elderly.